Heritage literacy - Babić, Darko muzeolog (2009)
The heritage literacy is a desirable and expected outcome of the heritage based education process. It has foundation in the comprehension of literacy as a state of having knowledge or competences in an explicit field and in comprehension of the heritage as a collective capital of (any) community. In it uttermost form heritage literacy is a form of life-long learning, adapted to differences beneficiaries represent. Accordingly, it is obvious that heritage literacy falls much more into citizenship based education then any formal education process (although some part of it could be reached in latter too). The aim of the presentation is to explain the idea and main points of heritage literacy, its necessity and to present the possible outline of methodical heritage education.